Litter decomposition and nutrient release from monospecific and mixed litters: Comparisons of litter quality, fauna and decomposition site effects - Yang, Kai; Zhu, Jiaojun; Zhang, Weiwei; Zhang, Qian; Lu, Deliang; Zhang, Yakun; Zheng, Xiao; Xu, Shuang; Wang, G. Geoff (The Journal of ecology, 2022)
Litter decomposition and nutrient release are key processes for soil C and nutrient cycling. However, the relative importance of the effects of litter quality, fauna and decomposition site on litter decomposition remains poorly understood. Moreover, the macronutrient and micronutrient (C, N, P, K, Ca, Mg, Mn, Cu and Zn) release in the decomposition process are even less well‐known. In this study, we performed 5040 litterbag samplings of monospecific (Larix gmelinii, Acer mono, Quercus mongolica and Juglans mandshurica) and mixed (Larix with each broad‐leaved litter) litter treatments using litterbags with three mesh sizes (for different‐sized fauna) in four paired stands of natural secondary forests compared with adjacent Larix plantations in a temperate forest ecosystem in China. Litter decomposition rate and macronutrient and micronutrient release during decomposition were assessed. We found that variation in litter quality had a considerably greater effect on litter decomposition than fauna and decomposition site. The decomposition constant was significantly related to the initial litter Mg concentration and lignin/P ratio, suggesting the importance of the Mg content and lignin/P ratio in controlling litter decomposition in temperate tree species. We also showed that macrofauna significantly increased monospecific but not mixed litter decomposition. In addition, the decomposition site conditions further influenced monospecific litter decomposition. Furthermore, the litter quality significantly influences N and Mn release in both monospecific and mixed litters. Compared with Larix litter, the average of N and Mn increased 33.9% and 53.8% in three broad‐leaved litters, and 21.4% and 38.0% in three mixed litters respectively. Synthesis. Litter quality is a relatively more important factor than fauna and decomposition site for the decomposition of both monospecific and mixed litters when studied at a local scale in temperate forests. Moreover, litter decomposition enhanced in plantation sites with poor soil nutrient status, which has implications for C and nutrient cycling and long‐term below‐ground forest ecosystem functions. Litter quality is a relatively more important factor than fauna and decomposition site for the decomposition of both monospecific and mixed litters. Moreover, litter decomposition enhanced in plantation sites with poor soil nutrient status, which has implications for C and nutrient cycling and long‐term below‐ground forest ecosystem functions.